2003
DOI: 10.3390/80200251
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Ethanolamination and Ketalization of 3-Ph-2,4-diacetyl(diethoxycarbonyl)-5-hydroxy-5-methylcyclohexanones

Abstract: The reaction of 3-phenyl-2,4-diacetyl(diethoxycarbonyl)-5-hydroxy-5-methyl-cyclohexanones with ethanolamine and ethylene glycol proceeds regioselectively using the carbonyl group of the alicycle to produce the corresponding cyclohexenylethanolamines and dioxolanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…by condensation of acetylacetone or acetoacetic acid esters with aldehydes. These compounds are known for their important biological activities such as herbicidal, antibacterial, antifungal, convulsant, anticonvulsant, antiimplantation and antiasthmone, besides being useful in organic synthesis and in industry [5][6][7][8][9]. Thus, they are useful synthons in further synthetic endeavours, as they have multiple keto, hydroxy and ester functionalities, potentially available for further transformations.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…by condensation of acetylacetone or acetoacetic acid esters with aldehydes. These compounds are known for their important biological activities such as herbicidal, antibacterial, antifungal, convulsant, anticonvulsant, antiimplantation and antiasthmone, besides being useful in organic synthesis and in industry [5][6][7][8][9]. Thus, they are useful synthons in further synthetic endeavours, as they have multiple keto, hydroxy and ester functionalities, potentially available for further transformations.…”
Section: Introductionmentioning
confidence: 98%
“…The methods of further modification of the thus prepared cyclohexanones with mono-or polyfunctional nucleophiles are also well studied [20][21][22][23][24][25][26][27][28]. For instance, it was found that reactions of hydroxylamine [9], hydrazine [23,24], ethylenediamine [27], ethanolamine [8,26,27], ethylene glycol [4], substituted aromatic amines [20,21,25], tosylhydrazide [22] and benzidine [28] with diethyl-4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate give isoxazole, imidazole and 1,3-dioxolane rings, Schiff base condensation products, etc. Moreover, in some cases the cyclization processes depend on temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diethyl-1-isobutyl-9-hydroxy-9-methyl-7-phenyl-1,4-diazaspiro [4.5]decane-6,8dicarboxylate (compound I) synthesized as described by Magerramov et al, 2013 [4] and 2,4-Diacetyl-5-hydroxy-5-methyl-3-phenyl-N-oxyethyl-1-cyclohexenylamine (compound II) synthesized as described by Kriven'ko et al, 2003 [5] [4][5] Standard agar well diffusion method [6] was used to determine antifungal properties of test compounds at three different concentrations i.e. 0.3%, 0.1% and 0.05%.…”
Section: Methodsmentioning
confidence: 99%
“…Ⱦɢɚɥɤɨɤɫɢɡɚɦɟɳɟɧɧɵɟ E-ɤɟɬɨɥɵ ɰɢɤɥɨɝɟɤɫɚɧɨɜɨɝɨ ɪɹɞɚ ɡɚ ɫɱɟɬ ɩɨɥɢɮɭɧɤɰɢɨɧɚɥɶɧɨɫɬɢ ɢ ɨɫɨɛɟɧɧɨ ɛɥɚɝɨɩɪɢɹɬɧɨɝɨ ɪɚɫɩɨɥɨɠɟɧɢɹ ɤɚɪɛɨɧɢɥɶɧɵɯ ɝɪɭɩɩ ɩɪɟɞɨɫɬɚɜɥɹɸɬ ɛɨɝɚɬɵɟ ɫɢɧɬɟɬɢɱɟɫɤɢɟ ɜɨɡɦɨɠɧɨɫɬɢ ɞɥɹ ɤɨɧɫɬɪɭɢɪɨɜɚɧɢɹ ɧɚ ɢɯ ɨɫɧɨɜɟ ɲɢɪɨɤɨɝɨ ɤɪɭɝɚ ɩɪɨɢɡɜɨɞɧɵɯ ɦɨɧɨɢ ɛɢɰɢɤɥɢɱɟɫɤɨɝɨ ɫɬɪɨɟɧɢɹ ɫ ɪɚɡɥɢɱɧɵɦ ɬɢɩɨɦ ɝɟɬɟɪɨɚɬɨɦɨɜ [1][2][3][4][5][6][7][8]. ȼ ɥɢɬɟɪɚɬɭɪɟ ɩɪɟɜɪɚɳɟɧɢɹ ɩɪɨɞɭɤɬɨɜ ɞɟɝɢɞɪɚɬɚɰɢɢ ɷɬɢɯ E-ɤɟɬɨɥɨɜ -ɞɢɚɥɤɨɤɫɢɡɚɦɟɳɟɧɧɵɯ ɰɢɤɥɨɝɟɤɫɟɧɨɧɨɜ ɧɟ ɢɫɫɥɟɞɨɜɚɥɢɫɶ, ɚ ɦɟɠɞɭ ɬɟɦ ɧɚɥɢɱɢɟ ɧɟɩɪɟɞɟɥɶɧɨɝɨ ɤɟɬɨɧɧɨɝɨ ɮɪɚɝɦɟɧɬɚ ɜ ɫɨɫɬɚɜɟ ɷɬɢɯ ɫɨɟɞɢɧɟɧɢɣ ɜ ɪɟɚɤɰɢɹɯ ɫ ɚɦɢɧɧɵɦɢ ɧɭɤɥɟɨɮɢɥɚɦɢ ɦɨɝɭɬ ɜɵɡɜɚɬɶ ɨɛɪɚɡɨɜɚɧɢɟ ɩɪɨɞɭɤɬɨɜ ɤɚɤ ɩɪɢɫɨɟɞɢɧɟɧɢɹ ɩɨ ɤɪɚɬɧɨɣ ɫɜɹɡɢ ɋ=ɋ, ɬɚɤ ɢ ɤɨɧɞɟɧɫɚɰɢɢ ɩɨ ɤɚɪɛɨɧɢɥɶɧɨɣ ɝɪɭɩɩɟ ɚɥɢɰɢɤɥɚ.…”
unclassified